2020
DOI: 10.3126/mjpahs.v3i2.35616
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Practice of Endodontic Treatment Protocols among General Dental Practitioners in Pokhara, Nepal

Abstract: Introduction: Endodontics is specialty field, but the majority of endodontic treatment in Pokhara is provided by the general dental practitioners. The aim of this study was to assess the practice of endodontic treatment protocols among general dental practitioners in Pokhara, Nepal. Materials and Methods: A cross sectional questionnaire based study was conducted among all the general dental practitioners working in various government, private hospital and clinic of Pokhara. Information about the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
3
2
Order By: Relevance
“…The present study recommended that rubber dam application is a mandatory step that was preferred by most of the respondents 231 (74.0%), it was supported by the fact that most practitioners were working in the private sector instead of government hospitals. These findings were not corroborated with research conducted in Nepal, [ 38 ] in which it was claimed that only 10.97% of GDPs use rubber dams regularly and did not follow the standards of endodontic principles. The results of this study are very much consistent with other studies [ 37 , 39 ].…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The present study recommended that rubber dam application is a mandatory step that was preferred by most of the respondents 231 (74.0%), it was supported by the fact that most practitioners were working in the private sector instead of government hospitals. These findings were not corroborated with research conducted in Nepal, [ 38 ] in which it was claimed that only 10.97% of GDPs use rubber dams regularly and did not follow the standards of endodontic principles. The results of this study are very much consistent with other studies [ 37 , 39 ].…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, no one respondent supported the tactile sensation in order to determine the working length. These findings were not in accordance with the study by Manandhar et al, which demonstrated that most GDPs (96.34%) used radiograph to ascertain working length, however, 6.09% believed in the tactile sensation technique, while 8.53% applied an apex locator followed by radiographic confirmation [ 38 ]. This study is consistent with research conducted by Shrestha et al [ 41 ] and Iqbal et al [ 24 ].…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…To accurately estimate the probability of the exceedance of flood events in a region, it is crucial to examine the historical records of past floods [56,91]. To accomplish this, it is essential to have an inventory map that documents flood occurrences in the area [92].…”
Section: Flood Inventorymentioning
confidence: 99%